The Impact of Service Quality, Price Perception, and Promotion on Customer Satisfaction at Alita Motor Workshop in Bangah Village, Sidoarjo - Alfernando Marga Putra; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the impact of service quality, price perception, and promotion on customer satisfaction at Alita Motor Workshop in Bangah Village, Sidoarjo. The research method used is a survey with a questionnaire distributed to customers of Alita Motor Workshop. The collected data is analyzed using regression methods to identify the relationships between these variables. The results indicate that service quality, price perception, and promotion significantly affect customer satisfaction. The implications of these findings can help Alita Motor Workshop improve its service strategies, pricing, and promotion to strengthen customer satisfaction in the local market.